LUCIFER - LBT NIR spectroscopic utility with camera and integral-field unit for extragalactic research - Mandel, H; Appenzeller, I; Seifert, W; Xu, W; Herbst, T; Lenzen, R; Thatte, N; Lemke, R; Bomans, D; Nicklas, H; Weiser, P (1999)
We propose to build a NIR imager/spectrograph for the LET which will support (1) seeing and diffraction limited direct imaging, (2) seeing and diffraction limited long-slit spectroscopy, (3) integral field spectroscopy and (4) tin small fields) OH-suppressed imaging of very faint objects. The instrument will cover the zJHK spectral bands with optimization for the K band. Therefore the optics will be cold (77 K). Whether the wavelength coverage can be extended to 5 mu without seriously compromising the K-band performance will be investigated during the design phase. At present a 2048 x 2048 HgCdTe array is foreseen as detector. Space will be reserved for the possibility of adding a (cold) multiple object spectroscopy unit. The feasibility of such a device will be investigated in parallel to the development of the main instrument. Six German institutes will cooperate to develop this LBT instrument.